Diagnostic and treatment features of ischemic heart disease in women. «The institute of therapy named after L. T. Maloy of UAMS» - V. I. Volkov; A. S. Isayeva (Атеросклероз, 2011)
The overview summarizes modern data concerning ischemic heart disease in women. Diagnostic and therapy features of disease are considered from the gender medicine points of view. Not only theoretical data are given in the paper, but also their clinical practical possible use.